An open label comparison of efficacy of low dose topiramate with naltrexone in preventing alcohol relapse - Marahatta, K.; Ma, J.; Pradhan, P.M.S.; Chapagain, M.; Tulachan, P; Sharma, V.D. (Journal of Psychiatrists’ Association of Nepal, 2017)
Introduction: Alcohol use disorder is a relapsing and remitting disorder. Preventing alcohol relapses has been a difficult task. The available drugs do not have adequate outcome in diverse needs. Topiramate, a GABAergic anticonvulsant, has been useful for the prevention of alcohol relapse as demonstrated in western studies. We compared the efficacy of Topiramate at 100mg with Naltrexone 50 mg in preventing relapse among Nepalese alcohol dependence patients. Methods: Following an inpatient alcohol detoxification, 37 patients taking Topiramate 100 mg and 41 patients taking Naltrexone 50 mg were followed up as outpatients at 1, 4, 8 and 12 weeks in order to monitor their abstinence period, craving for alcohol and alcohol use pattern. Results: At the end of 12 weeks follow up, Topiramate is as good as Naltrexone 50 mg in terms of maintaining abstinence (27% vs 31.7%, p=0.651) and reducing the daily alcohol intake. Topiramate is better than Naltrexone in decreasing craving at 12 wks (p=0.015). Conclusion: Topiramate 100 mg is equally efficacious to Naltrexone 50 mg in reducing alcohol craving and maintaining abstinence.